At Work in Meadowvale Village - McIlwraith, Thomas (Ontario History)

(untitled) (The Ontario Historical Society, 2016)
Ontario’s industrial and working-class history has deep roots in the water-powered mills and factories that lined scores of streams throughout the province. Each site drew its cluster of dwellings, general stores, church sanctuaries, travellers’ rests and more. Meadowvale village, founded in the 1830s on the Credit River in Mississauga, is one of these places, and, not simply by chance, it continues to display its mill village vernacular landscape generations after its industrial heyday has passed. Thanks to a community of energetic volunteers responding to opportunities provided by the Ontario Heritage Act (1974), plus a receptive civic administration, this gem of traditional Ontario has withstood suburbanization as it swept across the region. Meadowvale flourishes in the twenty-first century as a distinctive residential enclave in a huge sprawling city.